Analysis of Multi-Sensor Fusion Technology Applied in Autonomous Navigation - Li, Shouzheng (Exploring Science Academic Conference Series, 2026)
Aiming at the problems of perception blind zones, error accumulation, and poor environmental adaptability inherent in single -sensor autonomous navigation systems, this paper investigates multi -sensor fusion technology for autonomous navigation. By integrating LiDAR, vision, IMU, and GNSS/RTK sensors, a unified framework encompassing spatio -temporal registration, feature extraction, data fusion, and global optimization is constructed. Extended Kalman Filter (EKF) is employed to achieve tightly -coupled fusion, while graph optimization is utilized for SLAM correction. Path planning is realized based on the Dynamic Window Approach (DWA) and the Timed Elastic Band (TEB) algorithm. Experiments conducted in multiple scenarios demonstrate that the system achieves a positioning accuracy of 0.08 m in normal environments, better than 0.12 m in complex scenes, a tunnel trajectory deviation error of 0.064 m, and a lateral tracking error of ± 2.6 cm for agricultural machinery. The success rates for static and dynamic obstacle avoidance are 100% and 95.7%, respectively. This method can significantly improve navigation accuracy and robustness in complex environments, providing technical support for the autonomous navigation of intelligent equipment.